Ensino da compreensão leitora: faces e interfaces psicolinguísticas - Flôres, Onici Claro (2018)
The article is addressed to researchers and teachers interested in teaching reading comprehension, being analyzed by Psycholinguistics in their faces and interfaces. It examines different ways of reading with relation to the divergent context of the contemporary world. Discusses the importance of attention and working memory in the process of reading comprehension, according to that objective. Indicates, based on these analyses, pedagogical paths.